Tom Jaine (ed): The Good Food Guide 1993 - Davidson, Alan E (Petits Propos Culinaires, 1993)
Tom Jaine (ed): The Good Food Guide 1993: London, Consumers' Association and Hodder & Stoughton, 1992: over 720 pp, usual kit of introductory essays, maps, etc, £14.99.